1995
DOI: 10.1111/j.1476-5381.1995.tb15081.x
|View full text |Cite
|
Sign up to set email alerts
|

Mediation by prostaglandins of the nitric oxide‐induced neurogenic vasodilatation in rat skin

Abstract: 1 Intraplantar administration of the nitric oxide (NO) donor, sodium nitroprusside (SNP), induces hyperaemia in the rat paw skin, which is in part due to release of calcitonin gene-related peptide (CGRP) from afferent nerve fibres. The present study examined whether prostaglandins or other inflammatory mediators participate in the neurogenic vasodilatation caused by SNP. Blood flow in the plantar hindpaw skin of urethane-anaesthetized rats was measured by laser Doppler flowmetry. 2 The hyperaemic responses to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…17 Interactions between K ϩ channels and prostaglandins have also been documented. 10,11,13,35,36 We, therefore, explored the relative contributions of interactions between K ϩ channels, prostaglandins, and cGMP in mediating NO-evoked dilatation of ocular vasculature. Using retinal and choroidal vessel preparations as well as isolated cultured endothelial cells, we found that NO-induced relaxation of these oculovascular beds is partly mediated by cGMP but more importantly is dependent on PGI 2 formation by the endothelium through a mechanism mostly independent of guanylate cyclase, which involves opening a K Ca channel.…”
Section: Discussionmentioning
confidence: 99%
“…17 Interactions between K ϩ channels and prostaglandins have also been documented. 10,11,13,35,36 We, therefore, explored the relative contributions of interactions between K ϩ channels, prostaglandins, and cGMP in mediating NO-evoked dilatation of ocular vasculature. Using retinal and choroidal vessel preparations as well as isolated cultured endothelial cells, we found that NO-induced relaxation of these oculovascular beds is partly mediated by cGMP but more importantly is dependent on PGI 2 formation by the endothelium through a mechanism mostly independent of guanylate cyclase, which involves opening a K Ca channel.…”
Section: Discussionmentioning
confidence: 99%
“…Although CGRP receptors are present on endothelial and vascular smooth muscle cells, it seems that in skin, CGRP-induced dilation is largely independent of NO synthesis. 89,90 However, the vasoconstrictor effect of ET-1 is known to be limited by its dilator action exerted via ET B receptors on endothelium. 91 Thus, it needs to be established whether the depressed erythematous response to ET-1 and the depressed dilator response to cold per se reported in primary Raynaud's patients, reflects an impaired dilator influence of NO rather than a deficit of CGRP-containing nerves.…”
Section: Calcitonin Gene-related Peptide (Cgrp)mentioning
confidence: 99%
“…As mast cells are often juxtaposed to blood vessels and afferent nerve endings (Holzer, 1992) it could be hypothesized that interleukin-lß acts on these cells to stimulate the sequential formation of NO and prostaglandins which, in turn, contribute to the sensitization of afferent nerve endings. In addition, NO generated in the rat skin can by itself give rise to afferent nerve-mediated vasodilatation (Holzer and Jocic, 1994). Secondly, interleukin-1ß has been shown to stimulate the consecutive formation of NO and prostagtandin E 2 in vascular smooth muscle cells (lnoue et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The activity of N°-nitro-o-arginine methyl ester to elevate blood pressure, which has been noted previously (Holzer et al, 1993), is not understood at present. N°-nitro-L-arginine methyl ester was given systemically since this route of administration did not significantly diminish cutaneous blood flow, whereas local application of the drug has been observed to , reduce skin blood flow to a significant extent (Holzer and Jocic, 1994). The use of s.c. N°-nitro-L-arginine methyl ester was regarded as impractible, therefore, given that local N°-nitro-L-arginine methyl ester could inhibit vasodilator responses solely by virtue of its vasoconstrictor effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation